The Influence of Transactional and Transformational Leadership Styles on Employee Performance Through Job Satisfaction PT. PNM Pematang Siantar - Yandry Maroli; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
Effect of transactional leadership style and transformational leadership on employee performance through job satisfaction. Leadership Style relationship affecting employee Job Satisfaction, Transactional Leadership Style not affecting employee performance, Job Satisfaction affecting employee performance. Transformational leadership style affecting job satisfaction, Transformational Leadership Style affecting Job Satisfaction Transformational Leadership Style affecting Employee Performance